Low-dose sublingual immunotherapy compared to subcutaneous immunotherapy and conventional therapy in childhood asthma - Ariyanto Harsono (Indonesian Pediatric Society Publishing House, 2016)
Background Evidence begin to accumulate that high-dose sub- lingual immunotherapy (SLIT) is as effective as subcutaneous immunotherapy (SIT) in the treatment of childhood asthma. Since the capacity of sublingual area is similar whether the dose is high or low, the efficacy of low dose may be important to be studied. Objective To investigate the efficacy of low-dose sublingual im- munotherapy in the treatment of childhood asthma. Methods Parents signed informed consent prior to enrollment, after having received information about the study. Patients were moderate asthma aged 6-14 years with disease onset of less than 2 years before the commencement of the study and peak expiratory flow rate (PEFR) variability of more than 15%. Pa- tients were randomly allocated into group A, B, and C who received subcutaneous immunotherapy, low-dose sublingual immunotherapy, and conventional asthma therapy, respectively. Randomization was stratified into two strata according to age i.e., 6-11 years or 11-14 years. Patients of each stratum were randomized in block of three for each group. At the end of three months, lung function tests were repeated. The primary outcome was PEFR variability at the end of the study. The study was approved by the Ethics Committee of Soetomo Hospital Surabaya. Results Distribution of variants as represented by sex, age, eosinophil count, and total IgE concentration were normal in the three groups. PEFR variability decreased significantly from 16.97+0.81 to 8.50+5.08 and 17.0+0.87 to 8.40+4.72 in group receiving SIT and SLIT, respectively (p<0.05), but decreased not significantly from 17.00+0.83 to 10.82+0.5.41 in control group (p>0.05). Conclusion Low-dose SLIT is as efficacious as SIT in the treat- ment of moderate asthma in children